DIVIDEND POLICY ON FIRM PERFORMANCE: EVIDENCE FROM THE COMPANIES LISTED ON FTSE BURSA MALAYSIA TOP 100 INDEX - Nelly Phan, Wan Ying; Sharifah Sabrina, Syed Ali; Farah Dipah, Khalid; Farhana, Ismail; Norlina, Kadri (UNIMAS Publisher, 2025)
This research examines the impact of dividend policy on firm performance of the companies on the FTSE Bursa Malaysia Top 100 Index. It explores the relationship between key dividend policy indicators such as dividend payout ratio (DPR), dividend yield (DY), and dividend per share (DPS) and firm performance measures, including return on assets (ROA) and return on equity (ROE). The study employs a quantitative approach, analyzing secondary data from financial reports of the companies on FTSE Bursa Malaysia Top 100 Index from 2020 to 2024. Statistical methods, including multiple regression analysis, are used to identify trends and relationships. The findings highlight the dual role of dividend policy in influencing profitability. The study also identifies significant implications for financial managers, policymakers, and investors, offering insights into strategic decision-making for corporate growth and financial stability. With a sample of 72 companies on the FTSE Bursa Malaysia Top 100 Index that consistently pay dividends, these empirical results show that DPR is significantly negatively associated with firm performance. However, DY and DPS are significantly positively associated with firm performance. Overall, the study’s findings indicate that dividend policy significantly affects firm performance, suggesting that inconsistent or insufficient dividend payments can reduce firm value and weaken investor confidence, especially during volatile or post-crisis periods.